A Traceless Directing Group for CH Borylation1. Issue 49 (12th November 2013) - Preshlock, Sean M.; Plattner, Donald L.; Maligres, Peter E.; Krska, Shane W.; Maleczka, Robert E.; Smith, Milton R.
<x xml:space="preserve">Abstract</x> Not a trace: Borylation of the nitrogen in nitrogen heterocycles or anilines provides a traceless directing group for subsequent catalytic CH borylation. Selectivities that previously required Boc protection can be achieved; furthermore, the NBpin directing group can be installed and removed in situ, and product yields are substantially higher. Boc=tert‐butoxycarbonyl, pin=pinacolato.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>